Cervical Cancer Screening in Underserved Populations: Reflex versus Co-Testing for Cervical Cancer [16M]. (May 2018) - Heller, Michaela; Cottrell, Connie; Fish, Barry; Powell, Angela
Abstract : INTRODUCTION: Cervical cancer is the second most common cause of cancer mortality among women worldwide. Several studies concluded that cervical cancer screening and intervention programs should target communities with lower socioeconomic status due to lower rates of screening and knowledge. The Women's Health Center (WHC) at Akron General Cleveland Clinic hosts free bi-annual cervical cancer screenings. All patients are screened with simultaneous cytology and HPV testing as opposed to specific age and HPV reflex guidelines. The primary objective of this study is to determine the rate of positive HPV results in underserved women with normal cervical cytology to evaluate the benefit of initial co-testing. METHODS: Patients' charts were reviewed from inception of the program in October of 2006 to October 2014 to review cytology and HPV DNA results. Analysis was completed using descriptive statistics, which included prevalence rates of normal cytology with positive HPV testing. RESULTS: 512 women participated in the free screening program. Of the 512 women participating, 94% did not have insurance and 63.7% of them never had a previous pap smear. Of those, 70 had positive HPV results. The prevalence of negative cytology among women with positive HPV was 47% (n=33). Of these 72% (n=24) tested positive for high risk HPV strains and 22% (n=9) were positive for low risk HPV. CONCLUSION: Findings from this study have important implications in developing free and effective cervical cancer screening programs for lower socioeconomic women and the potential benefit for initial co-testing.